Detection of defects in reinforced concrete beams using modal data - Ismail, Z.; Razak, H.A.; Ibrahim, Z.; Rahman, A.G.A.; Hin, P.A. (2001)
A control reinforced beam and four reinforced concrete beams with various extent of defects in the form of voids and load-induced cracking were analyzed. Local flexural stiffness at each coordinate point was derived by substituting the regressed data at that point and using the centered-finite-divided-difference formula. The results of the first derivative of the local flexular stiffness for the reinforced concrete beams with voids were compared with those obtained from a similar beam with cracks in the middle. The results were also compared with a similar beam with cracks on the right side of the beam.